Persepsi Pemustaka Terhadap Layanan Sirkulasi Pada Perpustakaan Universitas Metamedia - Yovianda Safitri; Gustina Erlianti (Journal of Creative Student Research, 2024)
The purpose of this study was to describe how the effectiveness of circulation services at Metamedia University Library. The type of research to be used is quantitative research. This research method uses descriptive research methods. The population of this study were Metamedia University students. The sample used in this study was a random sampling sample which amounted to 91 respondents. The results of this study are: First, the reliability indicator obtained an average score of 2.95 is on a very good interval scale, which indicates the existence of reliability that can improve circulation services. Second, the responsibility indicator obtained an average score of 2.32 on the interval scale is not good, which shows the lack of responsibility possessed by circulation officers. Third, the human resources indicator obtained an average score of 2.94 on a good interval scale, which shows that there are good procedures in circulation services. Fourth, the facilities and infrastructure indicator obtained an average score of 1.81 on the interval scale is not good, which shows that the facilities and infrastructure provided by Metamedia University are still not good. Fifth, the accuracy indicator obtained an average score of 1.68 on the interval scale is not good, which shows that the timeliness of circulation services is still not precise and effective. Sixth, the efficiency indicator obtained from an average score of 1.57 is on a very unfavorable interval scale, which shows that the software application provided by the Metamedia University library is not sufficiently able to assist circulation staff. Seventh, the productivity indicator and the services provided obtained from the average score of 3.00 are on the good interval scale, which shows that the productivity and services provided to users have been carried out well. Eighth, the borrowing period indicator obtained from an average score of 2.95 is on a good interval scale, which shows the time of the borrowing period and the number of books borrowed is well done. Based on the results of this study, it can be concluded that the library's perception of circulation services at metamedia university is quite good.